Dutch Risk Classification and FIGO 2000 for Gestational Trophoblastic Neoplasia Compared. Issue 9 (November 2016) - Eysbouts, Yalcke Kjelle; Massuger, Leon; Thomas, Chris; Ottevanger, Petronella; Short, Delia; Harvey, Richard; Sebire, Neil; Kaur, Baljeet; Naveed, Sarwar; Sweep, Fred; Seckl, Michael
Abstract : Objective: Over the years, there has been a wide variety of classification systems in use worldwide to stratify patients between single-agent versus multi-agent chemotherapy, hindering comparison of international research results. The study presents a retrospective comparison of the International Federation of Gynecology and Obstetrics 2000 and Dutch risk classification system for gestational trophoblastic neoplasia. Methods and Materials: All patients diagnosed with gestational trophoblastic neoplasia between January 2003 and December 2012 at the trophoblastic disease centre in London were retrospectively scored according to the Dutch classification system (N = 813). Results: An extensive overlap between both scoring systems was seen, even though items and relative value of items were quite distinct. The Dutch system seems to be simpler and easier to apply in all situation; a degree of overtreatment can however be presumed with the use of either system. Conclusions: Although it is likely that outcome is indeed affected by the individual factors used in both systems, many factors relate to tumor bulk and may not be independently prognostic. We therefore believe that further refinement of the classification systems and their underlying prognostic items plus any new items that seem promising would be useful.